Blood testing in biathlon: observation of hematocrit values during competitive periods 1994-1997 - Manfredini, F.; Tschukin, A.; Moran, M.; Mongolini, C.; Buzzoni, D.; Haberstroh, J. (International Journal of Sports Medicine, 1999)
The International Biathlon Union, through its own Medical Commission, has undertaken a three-year program aimed at identifying the hematocrit levels of athletes who participate in biathlons. The purpose was to check for hematocrit levels exceeding normal physiological values as well as for any significant modifications within individuals during the course of the competitive season. All of the athletes registered in international biathlon races were, therefore, subjected to venous blood sampling (1 cc) three times a year prior to competition, in the days preceding two World Cup races (December and January) and the World Championships (February). The blood was centrifuged, the micro-hematocrit determined, and the value (rendered anonymous) recorded. This procedure was repeated for three consecutive competitive seasons (Dec. 1994-Feb. 1995, Dec. 1995-Feb. 1996, Dec. 1996-Feb. 1997). During this three-year period, the collected data showed a significant lowering of the average hematocrit level. In fact, from the first February sampling to the third February sampling, the average hematocrit value for the male population dropped from 48.04 +/- 2.36 to 46.33 +/- 1.91, and for the female population from 44.05 +/- 2.44 to 42.52 +/- 1.92. Even the distribution of the absolute hematocrit values was modified from the first to the third competitive season, especially for the February sampling, with a > or = 50% reduction for males and a > or = 48% reduction for females.